Analisis Yuridis Pemberian Kompensasi Pegawai Outsourcing Berdasarkan PP 35 Tahun 2021: Studi di PT Universal Karya Mandiri Batam - Tito Panji Nugroho; Soerya Respationo; Siti Nurkhotojah (CV Rewang Rencang, 2025)
This study analyzes the implementation of Government Regulation No. 35 of 2021 regarding outsourcing employee compensation in Batam City. Despite formal regulatory provisions for compensation, field implementation demonstrates inconsistency and ineffectiveness. Primary barriers include weak institutional supervision, low legal literacy among workers, and poor employer compliance. Premature contract termination practices to avoid compensation obligations contradict Aristotelian distributive justice principles. The research concludes that fair compensation requires regulatory clarity, institutional commitment, robust supervisory mechanisms, and enhanced worker rights awareness to achieve the regulation's normative objectives. Effective implementation necessitates comprehensive reform addressing systemic weaknesses in Indonesia's industrial relations framework, particularly concerning outsourced labor protection.